Challenges Affecting Implementation of Almajiri Model School Policy in Sabon Gari Local Government Area of Kaduna State - Suleiman, Juwaratu Yusuf; Buba, Ahmed; Patrick, Peter (Kashere Journal of Politics and International Relations, 2025)
The Almajiri System of Education has been age-long practice in the Northern States of Nigeria. It started as an organised and a well comprehensive system of education for learning Islamic principles and knowledge and as a centre well known in producing productive adults working toward the wellbeing of their immediate society. Unfortunately, the Almajiri system of education in Northern Nigeria is now been poorly managed which is threatening the security and the health care delivery system in the north. Many attempts have been made by government at different level to address the challenges caused by the Almajiri system of education but proved abortive. This study assessed the implementation of the Almajiri Model School system with empirical focus on Umaru Musa ‘Yar’adua Almajiri Bi-lingual Model Primary School, Maraban Gwanda, Sabon Gari Local Government Area of Kaduna State. Qualitative data was employed to collect data through the instrumentality of in-depth Interview and Focus Group Discussion. The study found that Sabon-Gari Local Government in spite of its financial challenges do contribute immensely in running the affairs of the school especially in the area of recruitment and payment of staff salary; payment of allowances to Qur’anic Teachers; and provision of teaching and administrative materials The study therefore, recommends among other things, that host communities should partner with security agencies to provide adequate security to the school community to guarantee effective teaching and learning.